The Influence of Ethnic, Gender, and Qualification of Directors on Company Performance - Rifki Putra Ananda; Desi Ilona; Anita Ade Rahma (UPI YPTK Journal of Business and Economics, 2021)
This study aims to determine the effect of ethnic, gender and qualification of the board of directors on company performance. Two control variable are quality audit and company age. The sample in this study was taken random at the companies listing on the Indonesia Stock Exchange, which were 266 companies with a study period of 7 years from 2011-2017. Data analysis by used panel data regression. The results of this study indicate that gender has a negative and significant effect on company performance, while ethnic and qualification have no significant effect on company performance. Quality audit and company age have no significant effect on company performance.